Case Report: Novel Biallelic Null Variants of SMPD4 Confirm Its Involvement in Neurodevelopmental Disorder With Microcephaly, Arthrogryposis, and Structural Brain Anomalies - Ji, Weigang; Kong, Xiangtian; Yin, Honggang; Xu, Jian; Wang, Xueqian (Frontiers in Genetics, 2022)
The SMPD4 gene encodes sphingomyelin phosphodiesterase 4, which preferentially hydrolyzes sphingomyelin over other phospholipids. Biallelic loss-of-function variants of SMPD4 have been identified in a group of children with neurodevelopmental disorder with microcephaly, arthrogryposis, and structural brain anomalies (NEDMABA). Here we report a girl of Chinese ancestry with intrauterine growth restriction, microcephaly, postnatal developmental delay, arthrogryposis, hypertonicity, seizure, and hypomyelination on brain magnetic resonance imaging; biallelic null variants (c.1347C>G[p.Tyr449*]; Chr2[GRCh37]: g.130877574_131221737del [whole gene deletion]) were detected by whole-exome sequencing. Our case is the first report of NEDMABA of Chinese ancestry, confirming the involvement of SMPD4 in NEDMABA and expanding the mutation spectrum of this syndrome.